2018
DOI: 10.1111/vox.12663
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of efficacy and safety of pathogen inactivated and quarantine plasma in routine use for treatment of acquired immune thrombotic thrombocytopenic purpura

Abstract: Cardiac and a spectrum of ECG findings are common in TTP. In this study, IBSP and QP had similar therapeutic profiles for TPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In our small cohort OctaplasLG® provided remission rates consistent with those reported recently in terms of number of TPE and plasma volume [19,21]. The systematic use of early adjuvant immune therapy like corticosteroids and rituximab dramatically decreased the number of TPE to achieve remission.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our small cohort OctaplasLG® provided remission rates consistent with those reported recently in terms of number of TPE and plasma volume [19,21]. The systematic use of early adjuvant immune therapy like corticosteroids and rituximab dramatically decreased the number of TPE to achieve remission.…”
Section: Discussionsupporting
confidence: 87%
“…In 2015, a retrospective French trial in iTTP patients has reported equivalence in terms of clinical efficacy and tolerance of blood bank SD-FFP and quarantine FFP, with a light superiority for SD-FFP in younger patients [18]. Some other retrospective studies comparing amotosaleninactivated plasma to quarantine of plasma showed no difference in term of efficacy [19,20]. Up to now, no study compared OctaplasLG® to another plasma product.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of the Phase III clinical development program for AI-FFP registration [44]. Another recent study carried out by our group reported comparable efficacy between AI-FFP and Q-FFP in iTTP [45].…”
Section: Discussionmentioning
confidence: 93%
“…One RCT (liver disease) and two observational studies (liver transplant and TTP) reported on thromboembolism as part of AE (none included prospective monitoring). No study reported significant differences in incidence rates of thromboembolism for PR versus conventional plasma …”
Section: Product Efficacymentioning
confidence: 99%
“…Synopsis: Nine observational trials and six RCTs were used to evaluate the safety of PR plasma. No study reported an increase in AE in PR plasma compared to conventional plasma and most reported similar or decreased AE.…”
Section: Product Efficacymentioning
confidence: 99%